Densely Packed Microgoblet Laser Pairs for Cross‐Referenced Biomolecular Detection. Issue 10 (8th June 2015) - Bog, Uwe; Brinkmann, Falko; Wondimu, Sentayehu Fetene; Wienhold, Tobias; Kraemmer, Sarah; Koos, Christian; Kalt, Heinz; Hirtz, Michael; Fuchs, Harald; Koeber, Sebastian; Mappes, Timo
<x xml:space="preserve">Abstract</x> Microgoblet laser pairs are presented for cross‐referenced on‐chip biomolecular sensing. Parallel readout of the microlasers facilitates effective mutual filtering of highly localized refractive index and temperature fluctuations in the analyte. Cross‐referenced detection of two different types of proteins and complete chemical transducer reconfiguration is demonstrated. Selective surface functionalization of the individual lasers with high spatial accuracy is achieved by aligned microcontact stamping.